TOURISM PROMOTION BROCHURE ON RECREATIONAL DESTINATION (LINGUISTICS PERSPECTIVE) - Afore Tahir Harefa; Nurul Hikmah Giawa; Dwi Putri Juwita Zebua; Erna Zamasi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study is motivated by the limited effectiveness of tourism promotional media at 101 Nusa Lima Beach in representing destination potential as well as sustainable tourism values. This study aims to develop a tourism promotion brochure that has high communicative effectiveness while supporting the strengthening of sustainability-oriented local tourism development. A Research and Development (R&D) approach adapted from Borg and Gall was used with the stages of needs analysis, planning and design, initial product development, expert validation, revision, and final product presentation. Data collection was conducted through field observation, interviews with tourism stakeholders and visitors, and documentation to identify tourism potential, visitor information needs, and promotional constraints encountered. The brochure was developed by emphasizing clarity of information regarding tourist attractions, facilities, accessibility, and operating hours, as well as using persuasive language and visual elements that support destination image formation. The expert validation process involving academics and tourism practitioners was carried out to assess content feasibility, accuracy of language use, and media design quality. The results of the study show that the brochure produced was declared valid and feasible to be used as a promotional medium after a number of minor revisions.The final product integrates sustainable tourism messages that are aligned with the Sustainable Development Goals (SDGs) with the aim of increasing destination visibility, strengthening promotional communication, and supporting sustainable local tourism development. These findings affirm that the development of promotional media based on linguistic studies and sustainability can function as an effective communication strategy for emerging coastal destinations. ABSTRAK Penelitian ini dilatarbelakangi oleh keterbatasan efektivitas media promosi pariwisata di Pantai 101 Nusa Lima dalam merepresentasikan potensi destinasi serta nilai-nilai pariwisata berkelanjutan. Studi ini bertujuan mengembangkan brosur promosi pariwisata yang memiliki daya komunikatif tinggi sekaligus mendukung penguatan pariwisata lokal yang berorientasi pada keberlanjutan. Pendekatan Research and Development (R&D) yang diadaptasi dari Borg dan Gall digunakan dengan tahapan analisis kebutuhan, perencanaan dan perancangan, pengembangan produk awal, validasi ahli, revisi, dan penyajian produk akhir. Pengumpulan data dilakukan melalui observasi lapangan, wawancara dengan pemangku kepentingan pariwisata dan pengunjung, serta dokumentasi untuk mengidentifikasi potensi wisata, kebutuhan informasi wisatawan, dan kendala promosi yang dihadapi. Brosur dikembangkan dengan menitikberatkan kejelasan informasi mengenai daya tarik wisata, fasilitas, aksesibilitas, dan jam operasional, serta menggunakan bahasa persuasif dan elemen visual yang mendukung pembentukan citra destinasi. Proses validasi ahli yang melibatkan akademisi dan praktisi pariwisata digunakan untuk menilai kelayakan konten, ketepatan penggunaan bahasa, serta kualitas desain media. Hasil penelitian menunjukkan bahwa brosur yang dihasilkan dinyatakan valid dan layak digunakan sebagai media promosi setelah dilakukan sejumlah penyempurnaan minor. Produk akhir mengintegrasikan pesan-pesan pariwisata berkelanjutan yang selaras dengan Sustainable Development Goals (SDGs) dengan tujuan meningkatkan visibilitas destinasi, memperkuat komunikasi promosi, serta mendukung pengembangan pariwisata lokal secara berkelanjutan. Temuan ini menegaskan bahwa pengembangan media promosi berbasis kajian linguistik dan keberlanjutan dapat berfungsi sebagai strategi komunikasi yang efektif bagi destinasi pesisir yang sedang berkembang.